The Growth of Banana Cv. Barangan as a Results of Aclimatization with Variaous In Cow Manure Planting Media: Pertumbuhan Pisang Barangan Hasil Aklimatisasi dengan Penggunaan Variasi Media Tanam Pupuk Kandang Sapi - Vidi Mercyana; Anditya Gilang Rizky Pradana (Agrifarm : Jurnal Ilmu Pertanian, 2025)
Abstract Banana (Musa sp) is one of the tropical fruit types originating from Southeast Asia. Bananas have a high enough potential to be managed intensively, because they have become an export and import trading business in the international market.Tissue culture is a method of plant propagation conducted vegetatively in a synthetic medium under sterile conditions (in vitro). Acclimatization is a period of adaptation of plantlets from in vitro (controlled environment) culture media to the open spaces before being planted in the field. One of the factors that influence the success of plantlets acclimatization is the use of the right media composition so that it can produce good plants. This study was conducted to determine the effect of growth of bananas (Musa acuminnata cv. Barangan) resulting from acclimatization with the use of variations in cow manure growing media. The research was using a completely randomized design (CRD) with a single factor. The factor was the treatment of planting media composition (soil: husk: cow manure) consisting of 8 levels: S1 = 1:1:1, S2 = 1:1:2, S3 = 1:2:1, S4 = 1:2:2, S5 = 2:1:1, S6 = 2:1:2, S7 = 2:2:1, S8 = 4:2:1. Variables observed included plant height, leaf number, leaf length, leaf width, and stem diameter. Data were analyzed by analysis of various test levels of 5% and further analysis of Duncan's Multiple Range Test (DMRT). The results showed that the treatment comparison of the composition of the planting medium, soil: husk: cow manure did not significantly affect the growth of barangan banana plants. In the treatment of comparison of the composition of soil: husks: cow manure (1:2:1) gives higher results and better results on all variable variables observed Keywords: Growth; manure; tissue culture